(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Acrokeratosis verruciformis of Hopf is a rare genodermatosis with an autosomal dominant mode of inheritance. It is a disorder of keratinization, characterized by multiple, skin-colored keratotic lesions resembling warts typically observed on the dorsum of the hands and feet. Histopathologically, the lesion shows considerable hyperkeratosis, acanthosis, and papillomatosis, mimicking a "church spire", and a thickened granular layer. It arises in early life, often at birth or infancy and rarely transform to squamous cell carcinoma. A rare case of acrokeratosis verruciformis of Hopf with squamous cell carcinoma transformation is reported in the department of Dermatology and Venereology, Combined Military Hospital, Dhaka. A 36 year old lady presented with multiple verrucous, hyperkeratotic, dyspigmented papules and plaques on her both legs since her early childhood and ulcer developed on the hypertrophic plaque about 20 years after the initiation of cutaneous lesions. Lesions were asymptomatic in the initial stage and subsequently developed mild pruritus and occasional bleeding from the ulcer. Histopathological finding from verrucous plaque is compatible with Acrokeratosis verruciformis of Hopf and skin biopsy from ulcerated plaque is compatible with Squamous cell carcinoma. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 84-86